Geovisualization Tool on Urban Quality. Interactive Tool for Urban Planning - Eynard, Enrico; Santangelo, Marco; Tabasso, Matteo (TeMA - Journal of Land Use, Mobility and Environment, 2014)
This paper describes the implementation of a tool that enables to gather and compare data from different sources for the benefit of urban planners. The tool is easy to access on different types of devices (personal computers, tablet, smartphones) thus being easily available in many various situations from urban planners and decision makers. It may also be used to find correlations between different phenomena in different time frames, so that solutions to possible problems can be rapidly suggested. The paper shows the process of implementation of the tool and some examples of application to the city of Torino in Northern Italy, a city who dealt with several urban transformation in the last two decades.